Last patient of the night eaudiobook - Gerlacher, Gary (AJ Docker Medical Thriller, 2024)
" Last Patient of the Night is M*A*S*H* meets Detective Harry Bosch. It's a thriller that won't disappoint." —Gregory D. Lee, author of Stinger: An International Thriller The death of a nameless young woman in his emergency room spurs physician AJ Docker to seek answers. Together with his policeman friend and a police dog, he sets out on a quest for justice for his lost patient, but he discovers more questions than answers as he delves into the criminal world. Last Patient of the Night is an action-packed thriller interspersed with lighthearted stories from the emergency room, featuring a cast of interesting characters. Gary Gerlacher's experience as an emergency physician lends authenticity to the ER culture. His debut novel is the first in the AJ Docker series, and will leave you on the edge of your seat.